Multiple-Plant Firms: Comment - Leontief, Wassily W. (Quarterly Journal of Economics, 1947)
Journal Article Multiple-Plant Firms: Comment Get access Wassily W. Leontief Wassily W. Leontief Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 61, Issue 4, August 1947, Pages 650–651, https://doi.org/10.2307/1885054 Published: 01 August 1947